La datation du Contra Christianos de Porphyre. À propos d’un passage problématique d’Eusèbe de Césarée (Histoire ecclésiastique, VI, 19, 2) - Morlet, Sébastien (Revue d'études augustiniennes et patristiques, 2010)
Critics generally date the composition of the Contra Christianos to Porphyry’s sojourn in Sicily, and thus most often around 270 AD. This date stems only from a misreading of Eusebius’ testimony in the History of the Church, VI, 19, 2, where the allusion to Porphyry’s Sicilian sojourn is not a way to date his antichristian work, but rather the activity of the philosopher as a whole. All the arguments often put forward to favour a later date are not more convincing, but one should admit with T. D. Barnes that Eusebius’ text has generally been misunderstood. The only certainty is that the Contra Christianos was written between the publication of a work on which it depends, the History of the Ptolemies by Callinicus Sutorius (between the end of 270 AD and summer 272 AD), and the death of Porphyry himself, around 305 AD.